2009
DOI: 10.1007/s10529-009-0140-0
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced ascorbic acid accumulation in transgenic potato confers tolerance to various abiotic stresses

Abstract: L-ascorbic acid (Vitamin C, AsA) is an important component of human nutrition. Plants and several animals can synthesize their own ascorbic acid, whereas humans lack the gene essential for ascorbic acid biosynthesis and must acquire from their diet. In the present study, we developed transgenic potato (Solanum tuberosum L. cv. Taedong Valley) over-expressing L-gulono-gamma-lactone oxidase (GLOase gene; NCBI Acc. No. NM022220), isolated from rat cells driven by CaMV35S constitutive promoter that showed enhanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(79 citation statements)
references
References 26 publications
5
73
1
Order By: Relevance
“…Accumulating data indicate that increased AsA content could enhance tolerance to salt stress in plants (Hemavathi et al, 2010;Zhang et al, 2012); indeed, an AsA-deficient mutant showed sensitivity to salt stress (Huang et al, 2005). Therefore, it is reasonable that the higher AsA content in csn5b confers tolerance to salt stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating data indicate that increased AsA content could enhance tolerance to salt stress in plants (Hemavathi et al, 2010;Zhang et al, 2012); indeed, an AsA-deficient mutant showed sensitivity to salt stress (Huang et al, 2005). Therefore, it is reasonable that the higher AsA content in csn5b confers tolerance to salt stress.…”
Section: Discussionmentioning
confidence: 99%
“…Ascorbic acid (AsA; vitamin C) is an important plant-derived antioxidant and constitutes a major source of dietary vitamin C in humans; in plants, AsA plays important roles in growth, development, and stress responses (Smirnoff and Wheeler, 2000;Hemavathi et al, 2010;Zhang et al, 2012). AsA has been proposed to function as an enzyme cofactor in photosynthesis and the syntheses of ethylene, gibberellins, and anthocyanins.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, AsA level modulates plant growth and development through altering phytohormone and defense signaling (Pastori et al, 2003). It is known that elevated AsA level confers tolerance to abiotic stresses such as salt and heat stress (Hemavathi et al, 2010;Vacca et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…A half cup (61 g) serving of baked potato provides only about 8 mg of the recommended daily intake of 40-90 mg per day (USDA Nutrient Data Laboratory 2015). However, potato is capable of producing increased levels of ascorbate (Hemavathi et al 2010;Bulley et al 2012), leading to an opportunity to genetically enhance popular varieties to provide additional Vitamin C our diets. Bulley et al (2012) reported an up to threefold increase in ascorbate through the overexpression of a single potato gene, GDP-L-galactose phosphorylase.…”
Section: Nutritionmentioning
confidence: 99%